KOHESI GRAMATIKAL REFERENSI DALAM CERPEN KOMPAS BERBASIS KORTARA - Novela Otri; Syahrul Ramadhan; Tressyalina Tressyalina; Afnita Afnita (Universitas Batanghari, 2025)
This study aims to analyze grammatical cohesion in the form of references in three short stories from the October 2017 edition of Kompas: Sepucuk Amplop di Taman (Envelope in the Garden), Tanah Warisan Asal (Ancestral Heritage Land), and Toko Wong (Wong's Shop). The study focused on the types of grammatical references, such as personal and demonstrative references, used to establish coherence and coherence in the text. A qualitative descriptive approach was used based on the KORTARA corpus (Nusantara Referential Language Corpus) to identify and classify reference forms and their frequency. The analysis showed that the most dominant type of reference was the first-person singular